Metformin improves cancer immunotherapy by directly rescuing tumor-infiltrating CD8 T lymphocytes from hypoxia-induced immunosuppression - Finisguerra, V; Dvorakova, T; Formenti, M; Van Meerbeeck, P; Mignion, L; Gallez, B; Van den Eynde, BJ (BMJ Publishing Group, 2023)
Background Despite their revolutionary success in cancer treatment over the last decades, immunotherapies encounter limitations in certain tumor types and patients. The efficacy of immunotherapies depends on tumor antigen-specific CD8 T-cell viability and functionality within the immunosuppressive tumor microenvironment, where oxygen levels are often low. Hypoxia can reduce CD8 T-cell fitness in several ways and CD8 T cells are mostly excluded from hypoxic tumor regions. Given the challenges to achieve durable reduction of hypoxia in the clinic, ameliorating CD8 T-cell survival and effector function in hypoxic condition could improve tumor response to immunotherapies.